2020
DOI: 10.1038/s41586-020-2776-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic landscape of intestinal organoid regeneration

Abstract: The development of intestinal organoids from single adult intestinal stem cells in vitro recapitulates the regenerative capacity of the intestinal epithelium 1 , 2 . Here we unravel the mechanisms that orchestrate both organoid formation and the regeneration of intestinal tissue, using an image-based screen to assay an annotated library of compounds. We generate multivariate feature profiles for hundreds of thousands of organoids to quantitatively describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 46 publications
10
166
0
Order By: Relevance
“…For SSCs, significantly represented subnetworks form a super module pointing towards interleukin signaling and microbiota interaction through receptors for retinoic acid (RA) (RXRA/RARA), vitamin D (VDR), and aryl hydrocarbon (AHR) (Figure 3A,G; Figure S9F-H). Importantly, a recent paper reported exogenous RA signaling suppressed the YAP-dependent regenerative stem state and promoted absorptive cell differentiation, consistent with the "absorptive" identity of SSCs (Lukonin et al, 2020). We furthered gleaned signature genes from organoids under RA signaling activation and found similar genes, such as ALDOB, to be upregulated in SSCs ( Figure 3A).…”
Section: Neoplastic Cells In Conventional Adenomas and Serrated Polypsupporting
confidence: 69%
“…For SSCs, significantly represented subnetworks form a super module pointing towards interleukin signaling and microbiota interaction through receptors for retinoic acid (RA) (RXRA/RARA), vitamin D (VDR), and aryl hydrocarbon (AHR) (Figure 3A,G; Figure S9F-H). Importantly, a recent paper reported exogenous RA signaling suppressed the YAP-dependent regenerative stem state and promoted absorptive cell differentiation, consistent with the "absorptive" identity of SSCs (Lukonin et al, 2020). We furthered gleaned signature genes from organoids under RA signaling activation and found similar genes, such as ALDOB, to be upregulated in SSCs ( Figure 3A).…”
Section: Neoplastic Cells In Conventional Adenomas and Serrated Polypsupporting
confidence: 69%
“…Recent reports demonstrated a critical role of RXR signaling in the regulation of the regeneration state in intestinal organoids. 20 Interestingly, compared to organoids cultured in the 8C minus VPA/EPZ6438 condition, Hyper-organoids showed a slightly decreased expression of target genes of RXR signaling (Supplementary information, Fig. S10g, h).…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of regeneration is observed during the early stages of organoid formation from single stem cells, this regeneration process is transient which cannot persist during the growth of organoids. 20 In the gut, for example, regeneration of damaged intestinal epithelium differs significantly in cellular composition and stem cell function from normal intestinal epithelial homeostasis. 15,[21][22][23][24] Homeostasis of the intestinal epithelium primarily relies on active cycling of Lgr5 + crypt-base columnar cells (CBCs), which give rise to all the major intestinal epithelial cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, they also showed that ISLR is overexpressed in human tissues from patients with IBD and colorectal cancers, suggesting that inflammation drives the expression of ISLR. Finally, Lukonin et al (2020) used a single cell imaging platform to identify a novel role of the orphan retinoid X receptor RXR in IEC proliferation and differentiation. They found that RXR activation using all-trans retinoic acid or a chemical activator led to maturation and differentiation of enteroids, associated with Yap cytosolic localization.…”
Section: Control Of Iec Fate After Injury By Cdx2 and The Hippo Pathwaymentioning
confidence: 99%